Water and sediment quality of Batang Ai Reservoir - Tan, Ai Chin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Water and sediment quality can affect the aquatic organisms. Hence, this study was conducted to determine the water and sediment quality at two future aquaculture sites (C14 and D15), an abandoned aquaculture sites (B9) and at the confluence (A6) of Batang Ai River and Engkari River. This study was done in June 2014 and January 2015. The results show the dissolved oxygen falls into Class II of NWQS (5-7 mg/L) at 0.2-8 m depths. Thermocline happens at 8-13 m. Stations C14 and D15 recorded high five-day biochemical oxygen demand, total suspended solids, nitrate-nitrogen, nitrite-nitrogen, total ammonia nitrogen, total nitrogen in water and sediment, total phosphorus and total sulfide as well as the highest chlorophyll-a at 10 m. The highest soluble reactive phosphorus recorded at A6 at 10 m in both sampling months. B9 recorded the highest water content, organic matter, total organic carbon, clay and total phosphorus in sediment. Sediment texture of all stations was classed into clay. Overall, the water quality of these stations at 0.2 m and 10 m fall into Class II (76.5-92.7 mg/L) and III (51.9-76.5 mg/L) according to Water Quality Index, which are suitable for sensitive, common and tolerant aquatic species. Trophic state of this study was oligotrophic and mesotrophic. However, periodic management of the activities in Batang Ai Reservoir is required to sustain the development of aquaculture.